Numerical study on maximizing heat transfer and minimizing flow resistance behavior of metal foams owing to their structural properties - G, Trilok; N, Gnanasekaran (International journal of thermal sciences, 2021)
Despite many research works considering metal foams largely involving heat exchange applications, an overall comprehensive view on the performance of metal foams based on their structural properties is hitherto unaddressed in the literature. In the present work, an air forced convection-laminar flow in a vertical channel is considered in which a heated plate along with metal foam is placed at the center. The plate is subject to constant heat flux condition to assess the performance of aluminum metal foam based on their degree of inclination towards maximizing heat transfer and minimizing flow resistance behavior in a vertical channel corresponding to the combination of structural properties they possess. Heat transfer and flow phenomena pertaining to the metal foam are numerically modeled using Local Thermal Non-Equilibrium (LTNE) and Darcy–Forchheimer flow models, respectively to obtain key thermo-hydrodynamic parameters. Both the independent and the combined effects of foam structural parameters viz., porosity and pore density on Nusselt number and friction factor are discussed justifying the effects of interfacial specific surface area and interfacial heat transfer coefficient of fluid saturated foam samples. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) a multi attribute decision-making technique is applied to solve the multi objective function to determine the performance of metal foams measured on a scale of 0 to 1. Five distinct criteria are studied involving distributed weights of 0:1, 0.25:0.75, 0.5:0.5, 0.75:0.25 and 1:0 each representing amplitudes of varying importance given to maximizing heat transfer and minimizing flow resistance characteristics of metal foams. Global performance charts are obtained, featuring performance abilities of metal foam samples covering wide ranges of porosity ranging from 0.8 to 0.97 and pore densities ranging from 5PPI to 45PPI corresponding to a given criteria involving a specific weight distribution scenario. The present work provides performance characteristics of available as well as possible foam samples with an overview idea on the range of structural aspects of foam samples, where the enhanced ability of the foam to perform best in meeting the given criteria is witnessed. •To study the ability of metal foams to enhance heat transfer and curtail flow resistance.•Darcy–Forchheimer and LTNE models to predict fluid flow and heat transfer, respectively.•Effects of porosity and pore density on thermo-hydrodynamic perfromance.•TOPSIS method is applied to effectively depict performance of metal foams.•Global performance charts are presented for existing and possible foam samples.